Physiological and immunological study of hypertensive patients treated with candesartan - Ali, Salah Abd; Al-Jowari, Suha Abdul-Khaliq (Iraqi Journal of Science, 2025)
Hypertension is the primary cause of cardiovascular disease and early mortality globally, it is a complex feature Determined by many factors endogenous mechanisms, genetic factors, physiological systems and environmental exposures variances. In recent years, there has been growing scientific interest and research focused on the immunological aspects of antihypertensive medications. Among these, Candesartan has emerged as a prominent subject of study. It has been demonstrated to reduce the inflammatory reactions associated with hypertension. The present study was conducted at Imam Hussein Teaching Hospital in the holy city of Karbala from December 20, 2022 to May 22, 2023. There were three distinct groups in the study which are (G1) healthy people, (G2) those receiving medication other than candesartan for their hypertension and (G3) patients receiving candesartan treatment for hypertension to evaluate various physiological parameters in order to ascertain the impact of candesartan on these samples such as serum sodium, serum potassium, and Adiponectin, as well as the investigation of some immunological markers like Interleukin1( IL-1), Interleukin18( IL-18) and Tumor Necrosis Factor(TNF). The study findings showed statistically significant differences in the mean levels of TNF, Interleukin-1, Interleukin-18, serum sodium, serum potassium, and adiponectin between the study groups. The current study was designed to obtain more clarification of some physiological and Immunological parameters in Iraqi hypertensive patients treated with candesartan, and determine the essential role of some physiological parameters such as, (serum sodium, serum potassium, and adiponectin), and Immunological parameters such as, [pro- inflammatory cytokines like, Interleukin-1(IL-1), Interleukin-18, and Tumor Necrosis Factor alpha (TNF-α)]. The result of physiological parameters showed a high significant increasing (P<0.05) in the concentration of serum potassium level in group of hypertension patients treated with candesartan (G3) while the concentration of serum sodium and adiponectin showed a significant decreasing (P<0.05) in the same group (G3) compared with control healthy group(G1), and positive control group (G2). The results of Immunological parameters including Interleukin-1, Interleukin 18 and Tumor necrosis factor- alpha showed that there was a high significant increasing (P<0.05) in the concentration of control healthy group(G1), and positive control group (G2) compared with hypertension patients treated with candesartan (G3).